Planning A Fruit Shop Business Development Strategy "Nu Mesari Buah" Using SWOT Analysis and QSPM (Quantitative Strategic Planning Matrix) Method - Ni Komang Mela Tri Utari; Dita Naufallina; Bambang Suryanto; Ella Mayasari (West Science Business and Management, 2024)
This study employs SWOT analysis and QSPM method to develop a business strategy for "Nu Mesari Buah" fruit shop, focusing on internal and external factors affecting its competitiveness. Through qualitative analysis, including interviews, strengths like strategic location and fresh stock, weaknesses such as price fluctuations, opportunities such as increased demand, and threats like competition were identified. Quantitative evaluations using IFE and EFE matrices revealed stronger internal advantages and opportunities, indicating a favorable position for strategic planning. The IE matrix placed the shop in the Hold quadrant, suggesting market and product development strategies. QSPM prioritized strategies, with increasing goods availability before holidays ranked highest. This aims to meet rising demand by collaborating with local suppliers. Overall, the research offers insights for strategic planning in "Nu Mesari Buah" and similar businesses, albeit requiring gradual monitoring and evaluation for practical implementation, considering environmental and market dynamics.